Chimpanzee Extraversion scores vary with epigenetic modification of dopamine receptor gene D2 (DRD2) and early rearing conditions. Issue 12 (2nd December 2022) - Staes, Nicky; White, Cassandra M.; Guevara, Elaine E; Eens, Marcel; Hopkins, William D.; Schapiro, Steven J.; Stevens, Jeroen M.G.; Sherwood, Chet C.; Bradley, Brenda J
ABSTRACT: Chimpanzees have consistent individual differences in behaviour, also referred to as personality. Similar to human personality structure, five dimensions are commonly found in chimpanzee studies that show evidence for convergent and predictive validity (Dominance, Openness, Extraversion, Agreeableness, and Reactivity/Undependability). These dimensions are to some extent heritable, indicating a genetic component that explains part of the variation in personality scores, but are also influenced by environmental factors, such as the early social rearing background of the individuals. In this study, we investigated the role of epigenetic modification of the dopamine receptor D2 gene ( DRD2 ) as a potential mechanism underlying personality variation in 51 captive chimpanzees. We used previously collected personality trait rating data and determined levels of DRD2 CpG methylation in peripheral blood samples for these same individuals. Results showed that DRD2 methylation is most strongly associated with Extraversion, and that varying methylation levels at specific DRD2 sites are associated with changes in Extraversion in nursery-reared, but not mother-reared, individuals. These results highlight the role of dopaminergic signalling in chimpanzee personality, and indicate that environmental factors, such as social experiences early in life, can have long-lasting behavioural effects, potentially through modification of the epigenome. These findings add to the growing evidence demonstrating the importance of the experience-dependent methylome for the development of complex social traits like personality.